Beyond the Finish Line: Muscle Injuries in Athletic Competition - Rumini; Adi S; Kusuma, Donny Wira Yudha (Physical Education Theory and Methodology, 2024)
Objectives. The study aimed to compare the incidence of muscle injuries in the qualifying rounds, semifinals and finals in athletics. Materials and Methods. A total of 14 male and 12 female athletes who participated in all rounds (preliminaries, semifinals, and finals) of the 100 m, 200 m, and 400 m matches were analyzed over a 4-year period starting in 2021-2024. The female athletes were aged 22.4 ± 3.81 years, with a mean height of 167 ± 8.6 cm, and weight — 64.6 ± 17.5 kg. The male athletes were aged 23.4 ± 3.82, having an average height of 169 ± 8.3 cm, and weight — 66.4 ± 15.8 kg. A t-test was used to conduct comparative assessment of performance between finals, semifinals, and preliminaries for each gender and event. A 95% confidence interval was calculated separately for each gender, event, and round. Additionally, incidence rates were compared. The significance level was accepted at p < 0.05. Results. HMI (hamstring muscle injuries) incidence rate for female qualifiers was found to be 1.50 (1.05-1.95), semifinals — 1.33 (0.79-1.88), and the final — 1.91 (1.44-2.38). LLMI (lower limb muscle injuries) incidence rate among female qualifiers was 1.50 (0.58-2.42), semifinals — 1.00 (1.00-1.00), and the final — 1.55 (1.36-1.74). HMI incidence rate in male qualifiers was 0.50 (0.08-1.28), semifinals — 0.67 (0.77-2.10), and 1.00 (0.34-1.66) in the final. LLMI incidence rate for male qualifiers was 0.40 (0.28-1.08), semifinals — 0.24 (0.55-1.05), and the final revealed 0.60 (0.08-1.28). Conclusions. The highest incidence of muscle injury in all forms among men was observed in the all-round category. In women, hamstring muscle injuries occurred in the final, while lower limb muscle injuries were most prevalent in the preliminaries and semifinals.